Current approaches in second language acquisition research a practical guide - Gass, Susan M.; Mackey, Alison (Hoboken, New Jersey John Wiley & Sons, 2023)
"In their earlier book in the Guides to Research Methods in Language and Linguistics series, Research Methods in Second Language Acquisition: A Practical Guide, leading researchers Alison Mackey and Susan Gass brought together an international team of experts to provide an overview on the leading research methods in the field of second language acquisition research. Building on the foundations of that earlier text, Mackey and Gass have again assembled a team of experts to cover the latest and most cutting-edge research methods that all students and early-career researchers will need to know in order to develop their own projects and experiments"-- Provided by publisher.
Classroom research methods -- Formal theory-based methodologies -- Qualitative and interpretive approaches to date in L2 research -- Collecting and analyzing mixed methods data in L2 research -- Using foreign and second language learner corpora -- Collecting and analyzing L2 introspective data -- Collecting and analyzing L2 sociolinguistic data -- Psycholinguistic methods in second language research -- Collecting and analyzing L2 pragmatics data -- Collecing and analyzing individual differences data in foreign language learning -- Collecting and analyzing L2 data on neurocognitive mechanism -- Coding second language data validly and reliably -- How to run statistical analyses -- Advancing meta-analytic methods in L2 research -- How and why to conduct a replication study.
Includes bibliographical references and index.
Keywords: Second language acquisition -- Research -- Methodology